2001
DOI: 10.1039/b107861e
|View full text |Cite
|
Sign up to set email alerts
|

The aldol reaction of silyl enol ethers within a micro reactor

Abstract: We have demonstrated the use of silyl enol ethers in the aldol reaction within a micro reactor. Quantitative conversion of the silyl enol ether to a beta-hydroxyketone was observed in a 20 min period compared to traditional batch systems, where quantitative yields were only obtained when extended reaction times of 24 h were employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 10 publications
0
38
0
5
Order By: Relevance
“…Importantly, under these conditions, no per¯uorination of the substrates was observed, with only the mono¯uorinated derivatives being isolated. The authors report that the bulk¯uorination of ethyl 2-chloroacetoacetate 57 gives only a low conversion to 58,75 illustrating that the¯ow system is more ef®cient. This illustrates the catalytic effect of the¯uorinated metal surface.…”
Section: Gas Phase Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, under these conditions, no per¯uorination of the substrates was observed, with only the mono¯uorinated derivatives being isolated. The authors report that the bulk¯uorination of ethyl 2-chloroacetoacetate 57 gives only a low conversion to 58,75 illustrating that the¯ow system is more ef®cient. This illustrates the catalytic effect of the¯uorinated metal surface.…”
Section: Gas Phase Reactionsmentioning
confidence: 99%
“…Wiles et al 58 have recently demonstrated the use of silyl enol ethers in the aldol reaction within a micro reactor. Quantitative conversion of the silyl enol ethers to b-hydroxyketones was observed in 20 min compared to traditional batch systems, where quantitative yields were only obtained when extended reaction times of up to 24 h were employed.…”
Section: Burns and Ramshawmentioning
confidence: 99%
“…Single-phase systems have been widely reported (see for example review by Brivio et al [23]) to yield increased rates of reaction, yields, and selectivities in comparison to traditional batch-syntheses. For example, Haswell et al demonstrated that the aldol reaction between aldehydes and silyl enol ethers in the presence of tetrabutyl ammonium fluoride (TBAF) reaches completion in only 20 min while the batch reaction requires 24 h for the same result [24]. Haswell's group reported increased selectivity of the cis (Z) to trans (E) isomeric ratio of the product of Wittig reaction [25].…”
Section: Advantages Of Microflow Reactorsmentioning
confidence: 97%
“…由于传热效率高, 高温或低温反应其温度可分别降 低或升高 [16,17] ; 反应时间也可大大缩短 [18] . 对于急剧放 热反应, 反应热可以很快散去, 消除了热斑; 减少了副 反应, 且提高了产物的选择性、产率和纯度 [14] .…”
Section: 反应效率增加unclassified